Problematika Proses Pengadaan Tanah - Setiyo Utomo (Jurnal Justisia : Jurnal Ilmu Hukum, Perundang-undangan dan Pranata Sosial, 2020)
The land has a social function; therefore, everyone has the right to make the best use of the land, from the land for agriculture to land to develop an area. This paper aims to analyze land acquisition problems in the West Kutai Regency and forms of legal protection for the community against land acquisition. This research method is normative juridical research. The land is fundamental to support the sustainable development of an area to impact the community whose land is designated for development. The legal umbrella still constrains land acquisition in West Kutai Regency in the form of regional regulations that provide access to the land acquisition process in the West Kutai Regency. The absence of legality of land certificates becomes an obstacle for the government to carry out land acquisition to trigger agrarian conflicts. For this reason, land acquisition, of course, the community must have a sense of sincerity if the land has been included in development activities. However, the government must provide compensation for communities affected by regional development. The concept of land acquisition carried out in an area must have a regional regulation formation in advance. In the land acquisition process, the community knows the legal basis, and the government has a legal basis in land acquisition. Justice for communities affected by land acquisition's impact, the government, must have an ideal system to provide justice for the community in terms of land acquisition.